Simultaneously Enhanced Hydrophilicity and Stability of a Metal‐Organic Framework via Post‐Synthetic Modification for Water Vapor Sorption/Desorption. (30th September 2022) - Luo, Tian‐Yi; Park, Sunghwan; Chen, Tso‐Hsuan; Prerna; Patel, Roshan; Li, Xinyu; Ilja Siepmann, J.; Caratzoulas, Stavros; Xia, Zhiyong; Tsapatsis, Michael
Abstract: With increasing demands for high‐performance water sorption materials, metal‐organic frameworks (MOFs) have gained considerable attention due to their high maximum uptake capacities. In many cases, however, high overall capacity is not necessarily accomplishing high working capacity under operating conditions, due to insufficient hydrophilicity and/or water stability. Herein, we present a post‐synthetic modification (PSM) of MOF‐808, with di‐sulfonic acids enhancing simultaneously its hydrophilicity and water stability without sacrificing its uptake capacity of ≈30 mmol g −1 . Di‐sulfonic acid PSM enabled a shift of the relative humidity (RH) associated with a sharp step in water vapor sorption from 35–40 % RH in MOF‐808 to below 25 % RH. While MOF‐808 lost uptake capacity and crystallinity over multiple sorption/desorption cycles, the di‐sulfonic acid PSM MOF‐808 retained >80 % of the original capacity. PSM MOF‐808 exhibited good hydrothermal stability up to 60 °C and high swing capacity. Abstract : Metal‐organic frameworks (MOFs) with large pores often lack sufficient hydrophilicity and stability. A post‐synthetic modification of MOF‐808 with di‐sulfonic acids simultaneously enhances its hydrophilicity and stability while maintaining the high water‐sorption capacity, achieving high swing capacities practical for potential applications, such as water harvesting and adsorptive heat transformations.